AB0047 Expression of ifn type i responsive genes in a cardiovascular disease continuum of rheumatoid arthritis. (12th June 2018) - Burska, A.N.; Harrison, G.; Hensor, E.M.; El Sherbiny, Y.; Bissell, L.-A.; Fent, G.; Plein, S.; Andrews, J.; Vital, E.M.; Buch, M.H.
Abstract : Background: Rheumatoid Arthritis (RA) patients have a prominent increase in cardiovascular disease (CVD) not fully explained by traditional risk factors 1 . Interferons type 1 (IFN-I) have been associated with premature CVD in SLE 2 and are implicated in several aspects of atherosclerosis and acute coronary syndromes 3 . A subpopulation of RA patients also display a peripheral blood IFN-I signature from 25% to 65% 4, associated with clinical response to biologics 5 . The IFN-I signature association with CVD in RA remains unclear. Objectives: To analyse expression of interferon type 1 response genes (ISGs) along a cardiac MRI (CMR) phenotyped CVD continuum in patients with RA. Methods: PBMC samples from 94 RA patients and 21 healthy controls (HC) were obtained. RA patients were stratified based on CMR into: RA CMRneg (no CVD-RA, n=13), RA CMRpos (subclinical CVD-RA, n=54), and RA with clinical CVD (defined as history of cerebrovascular disease or ischaemic heart disease) (RA-CVD n=25). qPCR of ISGs was performed using TaqMan Gene Expression Assays on Biomark (Fluidigm) with compatible reagents. Factor analysis of Ct values from 51 genes was used to create scores by calculating median dCt for genes loaded by each factor. Results: RA cohort median(IQR) age 63 (13.3)yrs, 69% female, disease duration 148.7 (215.3)mths; HC age 43 (16.5)y, 62% female. Three IFN-I factors (IFN Score 1, 2, 3) were present in the dataset and were composed of 19, 21 and 7 genes respectively. The Jonckheere Tepstra test showed significant increases in expression of Score 2 across the 4 groups(p=0.002), consistent with a continuum, and multiplicity-corrected post-hoc analysis identified differences between HC and subclinical CVD (p=0.034), HC and RA-CVD (p=0.004); as well as between no CVD-RA and subclinical CVD-RA (p=0.034); and subclinical CVD-RA with RA-CVD (p=0.029). Scores 1 and 3 did not show consistent directional trends across all studied groups. In no CVD-RA expression of Score 1 and 2 positively correlated with CRP (rho=0.744, p=0.002 and rho=659, p=0.010 recspectively). Score 1 with Low-Density Lipoproteins (rho=0.527, p=0.044), Framingham 10y risk (rho=0.595, p=0.019) and Score 3 with Pulse Wave Velocity (rho=0.584, p=0.022). In subclinical CVD-RA score 3 expression negatively correlated with Left Ventricular mass (rho=−0.381, p=0.005), in RA-CVD score 3 expression positively correlated with Glucose (rho=0.724, p=0.042, Triglycerydes (rho=0.821, p=0.023) and Total Cholesterol/High-Density Lipoprotein ratio (rho=0.505, p=0.039). Conclusions: An IFN-I score (Score 2) emerged as a possible factor characterising progression along a CVD continuum in RA patients, from no CVD to subclinical and clinical CVD; also distinguishing between HC and RA with subclinical and clinical CVD. IFN –I is involved in metabolic disturbancies associated with CVD development in RA. These results warrant further evaluation to confirm the findings in a larger cohort. References: [1] Kaplan MJ. Curr. Opin. Rheumatol2006;18(3):289–297. [2] Somers EC, et al. PloS one2012;7(5):e37000. [3] de Winther MPJ. Arterioscler. Thromb. Vasc. Biol2016;36(2):217–218. [4] Rodríguez-Carrio J, et al. Front Immunol2018;8. [5] Thurlings RM, et al. Arthritis Rheum2010;62:3607–3614. Disclosure of Interest: None declared